How many fungi make sclerotia?. (February 2015) - Smith, Matthew E.; Henkel, Terry W.; Rollins, Jeffrey A.
Abstract: Most fungi produce some type of durable microscopic structure such as a spore that is important for dispersal and/or survival under adverse conditions, but many species also produce dense aggregations of tissue called sclerotia. These structures help fungi to survive challenging conditions such as freezing, desiccation, microbial attack, or the absence of a host. During studies of hypogeous fungi we encountered morphologically distinct sclerotia in nature that were not linked with a known fungus. These observations suggested that many unrelated fungi with diverse trophic modes may form sclerotia, but that these structures have been overlooked. To identify the phylogenetic affiliations and trophic modes of sclerotium-forming fungi, we conducted a literature review and sequenced DNA from fresh sclerotium collections. We found that sclerotium-forming fungi are ecologically diverse and phylogenetically dispersed among 85 genera in 20 orders of Dikarya, suggesting that the ability to form sclerotia probably evolved ≥14 different times in fungi.